High-load squat training improves sprinting performance in junior elite-level soccer players: a critically appraised topic - Lohmann, L. H.; Warneke, K.; Schiemann, S.; Faber, I. R. (International Journal of Athletic Therapy & Training, 2022)
Practical Question: Is high-load squat training beneficial in improving sprinting performance in junior elite-level soccer players? Clinical Bottom Line: There is Level 3 evidence to support the validity of high-load squat training as a measure to improve sprinting performance in junior male elite-level soccer players. All three studies included showed significant increases in soccer-related sprinting performance.